Moral Hazard : Does IMF Financing Encourage Imprudence by Borrowers and Lenders? - Phillips, Steven (Economic Issues; Economic Issues ;, 2002)
Examines the issue of moral hazard inrelation to IMF loans to countries in financial difficulties. Concerns about moral hazard have had a prominent place in recent discussions on how the architecture of the international financial system should be reformed and what the IMF's role should be.